2013
DOI: 10.1111/hdi.12041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of association between atherogenic index of plasma and intima‐media thickness of the carotid artery for subclinic atherosclerosis in patients on maintenance hemodialysis

Abstract: Incidence of cardiovascular diseases in the patients having chronic kidney disease (CKD) is between 25% and 60%. This increased rate is proposed to be associated with "accelerated atherosclerosis." Increased carotid intima-media thickness (CIMT) is a subclinical atherosclerosis marker. Small-dense low-density lipoprotein particles are a strong risk factor for atherosclerosis. It was shown that atherogenic index of plasma (AIP = log(TG/HDL-c)) is correlated with size of the lipoprotein particles. We investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 52 publications
4
49
0
2
Order By: Relevance
“…Although significant differences were observed between pre-and post-HD for age group >60 years, the other evaluated age groups, by LDL-C/apoB ratio, did not show LDL phenotype changes. The Atherogenic Index of Plasma (AIP) has been cited recently as a risk marker for atherogenic disease since it indirectly indicates sdLDL in HD patients [19] [47] [48]. Our study showed a significant reduction of AIP at age groups 30 -39 and 40 -49 years.…”
Section: F S Marques Et Al Journal Of Biophysical Chemistrysupporting
confidence: 55%
“…Although significant differences were observed between pre-and post-HD for age group >60 years, the other evaluated age groups, by LDL-C/apoB ratio, did not show LDL phenotype changes. The Atherogenic Index of Plasma (AIP) has been cited recently as a risk marker for atherogenic disease since it indirectly indicates sdLDL in HD patients [19] [47] [48]. Our study showed a significant reduction of AIP at age groups 30 -39 and 40 -49 years.…”
Section: F S Marques Et Al Journal Of Biophysical Chemistrysupporting
confidence: 55%
“…It has been suggested that AIP is less susceptible to variations in disease activity during longer periods of time. This makes it more attractive for use in cardiovascular risk prediction than lipid concentrations per se , especially in children with ESRD (8). Elevated AIP is connected with higher percent of remnant lipoproteins and small, dense LDL (sdLDL) particles (29, 30).…”
Section: Discussionmentioning
confidence: 99%
“…The Atherogenic Index of Plasma (AIP) was calculated according to the following equation: AIP=log(TG/HDL-C), with units for TG and HDL-C in mmol/L (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial dysfunction, arterial stiffness, and accelerated atherosclerosis are common in stable kidney transplant patients and may contribute to the high cardiovascular event rate [3,5,6]. Endothelial dysfunction, a prerequisite to atherosclerosis, encompasses numerous maladaptive alterations adversely affecting vascular tone, haemostasis, and inflammatory processes within the arterial wall [7].…”
Section: Introductionmentioning
confidence: 99%